ANALISIS BIAYA PERBAIKAN DAN PERAWATAN GEDUNG SEKOLAH SWASTA X - Stefanus, Stefanus (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2020)
Planning for building maintenance and repairs is necessary to maintain the building so that it can be used properly for a long period of time. Building maintenance and repairs are generally carried out by building management. In the school building also needed the role of building management in carrying out maintenance and building facilities. With the facilities and infrastructure of a good and well-maintained school building, it will make the value of the school high. This research was conducted by collecting secondary data from all costs of repair and maintenance of buildings in five X private school locations from 2016 - 2018, as well as the initial value of the building construction and data processed using Microsoft Excel. From the data obtained for total repair and maintenance value from five locations of private schools x for 3 years amounting to Rp. 12,107,423,758. The total value of the costs obtained maintenance and repair of Mechanical Electrical Plumbing (MEP) and architecture, to repair and maintain the foundation and structure of private schools X does not incur costs. For MEP maintenance and repair costs of Rp. 5,048,736,655 and architecture Rp. 7,058,687,103. One of the high value of maintenance and repair costs is due to the absence of procedures for repairing facilities and infrastructure. Maintenance and repair costs are only carried out if the facilities and infrastructure are damaged and cannot be used, and there is no routine maintenance schedule. One of the things that must be done by private school X is to improve the maintenance system carried out by building management so that it can reduce the cost of repairing facilities and keep the facilities and infrastructure in good condition.ABSTRAK Perencanaan perawatan dan perbaikan gedung sangat diperlukan untuk menjaga gedung tersebut agar dapat digunakan dengan baik untuk jangka waktu yang panjang. Perawatan dan perbaikan gedung pada umumnya dilakukan oleh manajemen gedung. Pada bangunan sekolah juga diperlukan peran manajemen gedung dalam melakukan perawatan saranan dan sarana bangunan gedung. Dengan sarana dan prasarana gedung sekolah yang baik dan terawat, akan membuat nilai dari sekolah itu tinggi. Penelitian ini dilakukan dengan mengumpulkan data sekunder dari seluruh biaya perbaikan dan perawatan bangunan gedung di lima lokasi sekolah swasta X dari tahun 2016 - 2018, serta nilai awal pembangunan gedung tersebut dan data diolah menggunakan Microsoft Excell. Dari data di dapat untuk nilai perbaikan dan perawatan total dari lima lokasi sekolah swasta x selama 3 tahun sebesar Rp. 12.107.423.758,-. Total nilai biaya tersebut didapat perawatan dan perbaikan Mechanical Electrical Plumbing (MEP) dan arsitektur, untuk perbaikan dan perawatan pondasi dan struktur sekolah swasta X tidak mengeluarkan biaya. Untuk biaya perawatan dan perbaikan MEP sebesar Rp. 5.048.736.655,- dan arsitektur sebesar Rp. 7.058.687.103,-. Besarnya nilai biaya perawatan dan perbaikan salah satunya dsebabkan karena tidak adanya prosedur untuk perbaikan sarana dan prasarana. Biaya perawatan dan perbaikan hanya dilakukan bila sarana dan prasarana sudah rusak dan tidak bisa dipakai, serta tidak adanya jadwal rutin perawatan. Salah satu yang harus dilakukan sekolah swasta X adalah dengan memperbaiki sistem perawatan yang dilakukan oleh manajemen gedung agar dapat mengurangi biaya perbaikan sarana dan tetap menjaga sarana dan prasarana dalam kondisi baik.